Estate Planning of Shari’ah-Compliant Digital Assets Among Malaysians: A Mixed-Methods Approach - Omoola, Sodiq O.; Abdul Manaf, Zati Ilham; Drs Nasrul, Muhammad Amrullah (International Journal of Islamic Economics and Governance, 2024)
This paper examines Malaysia’s regulatory landscape and public awareness of digital assets, focusing on individuals under 45. It highlights the lack of global regulatory development for digital assets and the overlooks the aspect of posthumous management. The research evaluates awareness, adoption, and understanding of digital asset regulations, emphasising legal and Shariʿah challenges in estate management. Using a mixed-methods approach, the study collected 86 responses via social media surveys supported by doctrinal legal research. Findings show high interest in digital assets among younger with only 11.3% of participant possessing understanding of Shari’ah-compliant digital assets, whereas 20.8% had moderate familiarity with relevant laws on the assets. The study calls for educational campaigns and clearer Shariʿah-compliant regulatory guidelines to enhance market confidence and bridge the digital literacy gap. It offers insights for policymakers and digital exchanges on managing digital assets posthumously and suggests future research on specialised digital estate planning services and regulatory impacts.